Safety and Efficacy of Ultrasound-Enhanced Thrombolysis: A Comprehensive Review and Meta-Analysis of Randomized and Nonrandomized Studies - Tsivgoulis, Georgios; Eggers, Jürgen; Ribo, Marc; Perren, Fabienne; Saqqur, Maher; Rubiera, Marta; Sergentanis, Theodoros N.; Vadikolias, Konstantinos; Larrue, Vincent; Molina, Carlos A.; Alexandrov, Andrei V. (Stroke (1970), 2010)
Background and Purpose— Ultrasound-enhanced thrombolysis is a promising new approach to facilitate reperfusion therapies for acute ischemic stroke. So far, 3 different ultrasound technologies were used to increase the thrombolytic activity of tissue plasminogen activator (tPA), including transcranial Doppler (TCD), transcranial color-coded duplex (TCCD), and low-frequency ultrasound. We performed a meta-analysis to evaluate the safety and efficacy of ultrasound-enhanced thrombolysis compared to the current standard of care (intravenous tPA). Subjects and Methods— Through Medline, Embase, and Cochrane database search, we identified and abstracted all studies of ultrasound-enhanced thrombolysis in acute cerebral ischemia. Principal investigators were contacted if data not available through peer-reviewed publication were needed. Symptomatic intracerebral hemorrhage (sICH) and recanalization rates were compared between tPA, tPA+TCD±microspheres (μS), tPA+TCCD±μS, and tPA+low-frequency ultrasound. Results— A total of 6 randomized (n=224) and 3 nonrandomized (n=192) studies were identified. The rates of symptomatic intracerebral hemorrhage in randomized studies were as follows: tPA+TCD, 3.8% (95% CI, 0%–11.2%); tPA+TCCD, 11.1% (95% CI, 0%–28.9%); tPA+low-frequency ultrasound, 35.7% (95% CI, 16.2%– 61.4%); and tPA alone, 2.9% (95% CI, 0%–8.4%). Complete recanalization rates were higher in patients receiving combination of TCD with tPA 37.2% (95% CI, 26.5%– 47.9%) compared with patients treated with tPA alone 17.2% (95% CI, 9.5%–24.9%). In 8 trials of high-frequency (TCD/TCCD) ultrasound-enhanced thrombolysis, tPA+TCD/TCCD±μS was associated with a higher likelihood of complete recanalization (pooled OR, 2.99; 95% CI, 1.70–5.25; P =0.0001) when compared to tPA alone. High-frequency ultrasound-enhanced thrombolysis was not associated with an increased risk of symptomatic intracerebral hemorrhage (pooled OR, 1.26; 95% CI, 0.44–3.60; P =0.67). Conclusions— The present safety and signal-of-efficacy data of high-frequency ultrasound-enhanced thrombolysis should be taken into account in the design of future randomized controlled trials.